HEAVY METAL CONCENTRATIONS IN Pseudotolithus typus AND Portunus validus, WATER AND SEDIMENT FROM TARKWA BAY, NIGERIA - LAWAL-ARE, A.O; BABARANTI, O. A. (Nigerian Journal of Fisheries, 2014)
Concentrations of copper, chromium, cadmium, iron, manganese, lead, and zinc were determined in crab, fish, water and sediment from Tarkwa Bay of Lagos lagoon using Atomic Spectroscopy (AAS). Samples were collected between January 2008 and June 2008. The physico-chemistry of water from Tarkwa Bay was moderately stable. Temperature ranged from 27-30 ⁰C, salinity from 30-35‰ and pH from 7.8-8.1 throughout the study period.Trace metals present were in insignificant concentrations in water and fish and in elevated concentrations in sediment and crab. Iron was the dominant metal while cadmium was the least abundant metal recorded. Cadmium was not detected in January in all samples. The mean chromium concentrations found in crab was 0.71 mg/kg, 0.69 mg/kg in fish, 3.76 mg/kg in sediment and 0.02 mg/l in water. There was a positive correlation of 0.97 and a negative correlation of -0.97 in chromium concentrations. Manganese concentrations in crab and fish were not significantly different. There were no significant differences in crab and fish; sediment and crab lead concentrations. The mean levels of zinc were 9.93 mg/kg, 5.03 mg/kg, 9.70 mg/kg and 0.07 mg/l in crab, fish, sediment and water respectively. There was a positive correlation of 0.81 between fish and sediment zinc concentrations and no significant differences exist between crab and sediment zinc concentrations.